Formulation and evaluation of Ocimum basilicum-based emulgel for wound healing using animal model - Barkat Ali Khan; Shafi Ullah; M.Khalid Khan; Sultan M Alshahrani; Valdir A Braga (Elsevier, 2020)
The main aim of the topically applied drugs is to provide local drug contact to the skin and minimize general absorption of drugs. Ocimum basilicum (OB) is popular for folk medicines, having official acceptance in many countries. The aim of this study was to formulate and evaluate the efficacy of topical application of OB-based emulgel on wound healing in animal model. The prepared formulations (OB emulgel) were assessed for FTIR analysis, stability studies, physical appearance, rheological behavior, spreadability, patch/sensitivity test and in vitro drug release. The in vivo wound healing effect was evaluated and compared with commercially available Silver Sulfadiazine cream Quench® in wound-induced rabbits by macroscopic and histopathological evidence. The OB extract/drug was compatible with the selected polymer and other excipients and indicated the suitability of the polymers/excipients for preparation of topical emulgel. The formulated OB emulgel exhibited good physical properties. The release profile of emulgel was satisfactory and released 81.71 ± 1.7% of the drug in 250 min. In vivo wound healing studies showed that OB emulgel exhibited the highest percent wound contraction similar to the commercial product (p > 0.05). This activity was statistically significant (p < 0.05) in comparison to control. Histopathological assessment showed marked improvement in the skin histological architecture after 16 days of OB emulgel treatment. In conclusion, the data demonstrated here signify the prospective of 5% OB emulgel as an innovative therapeutic approach in wound healing.